2016
DOI: 10.1016/j.scitotenv.2015.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to manganese in air: Associations with tremor and motor function

Abstract: Background Manganese (Mn) inhalation has been associated with neuropsychological and neurological sequelae in exposed workers. Few environmental epidemiologic studies have examined the potentially neurotoxic effects of Mn exposure in ambient air on motor function and hand tremor in adult community residents. Mn exposed residents were recruited in two Ohio towns: Marietta, a town near a ferro-manganese smelter, and East Liverpool, a town adjacent to a facility processing, crushing, screening, and packaging Mn p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 34 publications
2
31
0
1
Order By: Relevance
“…This study is part of a larger cross-sectional study assessing the neurotoxic effects of air-Mn in residents living near a ferromanganese smelter in Marietta, Ohio, and an open-air Mn storage and packaging facility in East Liverpool, Ohio ( Bowler, Adams, et al, 2016 ; Bowler, Beseler, et al, 2016 ; Bowler et al, 2012 ; Kim et al, 2011 ). Both Marietta and East Liverpool have been reported by the U.S. Environmental Protection Agency (EPA) to have some of the highest measured environmental concentrations of respirable air-Mn in the U.S. ( U.S. EPA, 2011 U.S. EPA, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger cross-sectional study assessing the neurotoxic effects of air-Mn in residents living near a ferromanganese smelter in Marietta, Ohio, and an open-air Mn storage and packaging facility in East Liverpool, Ohio ( Bowler, Adams, et al, 2016 ; Bowler, Beseler, et al, 2016 ; Bowler et al, 2012 ; Kim et al, 2011 ). Both Marietta and East Liverpool have been reported by the U.S. Environmental Protection Agency (EPA) to have some of the highest measured environmental concentrations of respirable air-Mn in the U.S. ( U.S. EPA, 2011 U.S. EPA, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional study design was used in this health study conducted in three Ohio towns (Bowler, Kornblith, et al 2015), two with reported high levels of Mn/A (Marietta and East Liverpool) and one town which is demographically similar, but unexposed to Mn/A (Mount Vernon). East Liverpool was reported by the U.S. Environmental Protection Agency (EPA) to have the highest measured concentrations of respirable Mn/A in the U.S. (U.S.…”
Section: Methodsmentioning
confidence: 99%
“…This methodology is further described in previous manuscripts (Bowler, Kornblith, et al 2015; Kim et al 2015). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations